2020
DOI: 10.1111/ijpo.12645
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a responsive parenting intervention on child emotional overeating is mediated by reduced maternal use of food to soothe: The INSIGHT RCT

Abstract: Summary Background Child emotional overeating is a risk factor for obesity that is learned in the home environment. Parents' use of food to soothe child distress may contribute to the development of children's emotional overeating. Objectives To examine the effect of a responsive parenting (RP) intervention on mother‐reported child emotional overeating, and explore whether effects are mediated by mother‐reported use of food to soothe child distress. Methods The sample included primiparous mother‐infant dyads r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…The majority of studies were conducted in the USA ( n = 20), 24–43 followed by Australia ( n = 10), 44–53 United Kingdom ( n = 8), 54–61 New Zealand ( n = 1), 62 Norway ( n = 2), 63,64 and Sweden ( n = 1) 65 . Thirty‐four studies, reported in 33 papers, employed a quantitative design, including RCTs of an intervention ( n = 5), 32,39,50,62,63 observational cohort studies ( n = 8), 24,27–29,35,54,59,60 cross‐sectional studies ( n = 11), 24,30,38,41–44,46,48,53,64 a case–control study, 26 a within‐subject experimental study, 40 a quasi‐experimental study, 51 and observational descriptive/measurement development 31 . Six studies undertook secondary analyses; two used cross‐sectional data, 25,37 two studies used data from observational cohort studies, 33,45 one used control group data, 34 and one used data from an RCT 36 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of studies were conducted in the USA ( n = 20), 24–43 followed by Australia ( n = 10), 44–53 United Kingdom ( n = 8), 54–61 New Zealand ( n = 1), 62 Norway ( n = 2), 63,64 and Sweden ( n = 1) 65 . Thirty‐four studies, reported in 33 papers, employed a quantitative design, including RCTs of an intervention ( n = 5), 32,39,50,62,63 observational cohort studies ( n = 8), 24,27–29,35,54,59,60 cross‐sectional studies ( n = 11), 24,30,38,41–44,46,48,53,64 a case–control study, 26 a within‐subject experimental study, 40 a quasi‐experimental study, 51 and observational descriptive/measurement development 31 . Six studies undertook secondary analyses; two used cross‐sectional data, 25,37 two studies used data from observational cohort studies, 33,45 one used control group data, 34 and one used data from an RCT 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Only one qualitative paper failed to meet the MMAT criteria for screening 56 : the majority clearly addressed the research questions 47,52,55,57,58,61,65 and derived their findings adequately from the data 47,49,52,55,57,58,61 . The randomised trials all conducted appropriate randomization and had comparable groups at baseline 32,36,39,50,62,63 . Three of the trials had low follow‐up, 32,39,63 and some of the included papers 32,36,39,50,62 did not report whether participants adhered to the assigned intervention, although this may have been reported elsewhere.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations